Health-care interventions to promote and assist tobacco cessation: a review of efficacy, effectiveness and affordability for use in national guideline development - West, Robert; Raw, Martin; McNeill, Ann; Stead, Lindsay; Aveyard, Paul; Britton, John; Stapleton, John; McRobbie, Hayden; Pokhrel, Subhash; Lester-George, Adam; Borland, Ron (Wiley, 2015)
Aims: This paper provides a concise review of the efficacy, effectiveness and affordability of health-care interventions to promote and assist tobacco cessation, in order to inform national guideline development and assist countries in planning their provision of tobacco cessation support.